Risk Evolution Study of Tailings Dam Failures Disaster Based on DEMATEL-MISM - Zheng, Binbin; Wang, Jiahe; Feng, Tingting; Wang, Wensong; Zhou, Yuxi; Cao, Guansen; Wang, Yufei (Frontiers in Earth Science, 2022)
Tailings pond engineering is a complex and extensive system with many risk factors. Clarifying the evolutionary relationships between the factors and strengthening effective management is important to reduce the risk of dam failure. This paper proposes an efficient and reliable method for analyzing the evolution of tailings dam failure risk. Firstly, 35 risk factors affecting tailings pond failure are summarized. An index system for evaluating the impact factors of dam breach is constructed from four aspects: personnel, management, environment, and system. Secondly, the Decision-making Trial and Evaluation Laboratory (DEMATEL) was used to study the influence relationships between the factors, and to analyze and identify the key causal factors. Subsequently, the Modified Interpretative Structural Model Method (MISM) was used to divide the cause factors into five levels of influence and to determine the level of integrated influence between the risk factors. Finally, an evolutionary model of tailings pond dam breach risk was constructed based on the analysis results. The results of the study show the following points. (1) System risk accounts for 57.17% of the total weight whereas personnel risk accounts for 16.64% of the total weight. To maintain the stability of the tailings pond system, in addition to focusing on system factors, personnel risk should not be ignored. (2) Rainfall intensity is an essential causal factor. Paying attention to rainfall intensity and taking appropriate measures can effectively reduce the risk of dam breach. The height of the stacking dam (X8) and the depth of the infiltration line (X9) account for a large proportion of the causal factors during the transition period, making controlling the height of the stockpile dam with accurate monitoring of the depth of the infiltration line can improve the stability of the dam. (3) In the tailings pond dam risk evolution model, there are 30 factors with higher mutability and correlation, and the risk transmission of these factors plays a transitional role. A risk factor transfer network diagram was established for this purpose as a diagnostic knowledge map. The research results can provide new methods and ideas for tailings dam failure risk analysis research and practice.